Analisis Kebersihan Air Kamar Mandi di Lingkungan Kampus 1 IAKN (Institut Agama Kristen Negeri) Tarutung - Angelia Putriana; Siti Aisyah; Apriliani Lase; Sabam Syahputra; Aprilana Lase (Yayasan Literasi Sains Indonesia, 2023)
This study aims to analyze the cleanliness of bathroom water in the environment of Campus 1 IAKN (Institut Agama Kristen Negeri) Tarutung. Bathroom water is a vital component in maintaining health and hygiene, making it essential to ensure its quality meets health standards. The research involved collecting water samples from various bathrooms on the campus and conducting laboratory tests to evaluate cleanliness parameters such as total coliform, Escherichia coli, pH, and turbidity. The test results indicated that most of the bathroom water samples met cleanliness standards; however, some samples showed results beyond safe limits, particularly concerning coliform and turbidity. The analysis also identified factors contributing to contamination, including inadequate maintenance of the sanitation system and suboptimal waste disposal. These findings highlight the importance of improving the sanitation system and enhancing maintenance procedures to ensure better quality bathroom water. Recommendations include increasing maintenance frequency, using better filtration technology, and raising awareness about the importance of sanitation among users. This study is expected to contribute to efforts in improving cleanliness and health standards in the campus environment